Gambaran Kadar Glukosa Darah Dengan Pemberian Ekstrak Metanol Kunyit Hitam ( Curcuma Caesia )Pada Mencit Yang Diinduksi Aloksan - Sri Kartini; vonny kurnia utama; rismawati (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Diabetes mellitus (DM) is a disease characterized by an increase in blood glucose levels due to the body's inability to regulate glucose levels. DM has two types: type 1 diabetes, which results from an autoimmune reaction against pancreatic cell proteins, and type 2 diabetes, which is caused by a combination of genetic factors related to insulin secretion disorders and environmental factors such as obesity and overeating. One alternative treatment involves using black turmeric (Curcuma caesia), known for its antidiabetic properties.This study aims to conduct a phytochemical screening and determine the effective dose of methanol extract of black turmeric in reducing blood glucose levels in alloxan-induced mice. The research used an experimental method with a glucometer. A total of 24 mice were divided into six groups, with four mice in each group. The phytochemical screening results showed the presence of alkaloids, flavonoids, saponins, tannins, and triterpenoids. Data analysis was performed using ANOVA, followed by the Kruskal-Wallis non-parametric test. The blood glucose measurements showed that Group 1 (Na-CMC 1%) had 224.25±41.61 mg/dl, Group II (glibenclamide 5 mg) had 101±4.78 mg/dl, Group III (dose 1, 10 mg/kgBW) had 175.25±17.25 mg/dl, Group IV (dose 2, 25 mg/kgBW) had 149.75±9.10 mg/dl, and Group V (dose 3, 40 mg/kgBW) had 115±10.16 mg/dl. Based on the study results, the methanol extract of black turmeric at dose 3 (40 mg/kgBW) effectively reduced blood glucose levels over 15 days, making it the most effective dose.